Imagining the future: memory, simulation, and beliefs - Bordalo, Pedro; Burro, Giovanni; Coffman, Katherine B.; Gennaioli, Nicola; Shleifer, Andrei (The review of economic studies, 2025)
How do people form beliefs about novel risks, with which they have little or no experience? Motivated by survey data on beliefs about COVID we collected in 2020, we build a model based on the psychology of selective memory. When a person thinks about an event, different experiences compete for retrieval, and retrieved experiences are used to simulate the event based on how similar they are to it. The model predicts that different experiences interfere with each other in recall and that non-domain-specific experiences can bias beliefs based on their similarity to the assessed event. We test these predictions using data from our COVID survey and from a primed-recall experiment about cyberattack risk. In line with our theory of similarity-based retrieval and simulation, experiences and their measured similarity to the cued event help account for experience effects, priming effects, and the interaction of the two in shaping beliefs.
Online verfügbar: 27. Juni 2024, Korrektur und Schriftsatz: 2. August 2024
Gesehen am 23.06.2025
Keywords: Aufsatz in Zeitschrift